COVID-19 related mental health issues: a narrative review of psychometric properties of scales and methodological concerns in scale development. (June 2021) - Ransing, Ramdas; Dashi, Elona; Rehman, Sajjadur; Mehta, Varun; Chepure, Ashish; Kilic, Ozge; Hayatudeen, Nafisatu; Orsolini, Laura; Vahdani, Bita; Adiukwu, Frances; Gonzalez-Diaz, Jairo M; Larnaout, Amine; et al.
Objectives: The global crisis of COVID-19 and its consequential strict public health measures placed around the world have impacted mental health. New scales and tools have been developed to measure these mental health effects. This narrative review assesses the psychometric properties of these scales and tools and methodological aspects of their development. Methods: PubMed, PubMed Central, and Google Scholar were searched for articles published from 15 May 2020 to 15 August 2020. This search used three groups of terms ("tool" OR "scale" AND "mental" OR "psychological"; AND "COVID-19" OR "coronavirus"). The identified scales were further evaluated for their psychometric properties and methodological aspects of their development. Results: Though the studies developing these scales ( n = 12) have demonstrated their robust psychometric properties, some methodological concerns are noteworthy. Most of the scales were validated using internet-based surveys, and detailed descriptions of the mode of administration, sampling process, response rates, and augmentation strategies were missing. Conclusions: The heterogeneous and inadequate reporting of methods adopted to evaluate the psychometric properties of the identified scales can limit their utility in clinical and research settings. We suggest developing guidelines and checklists to improve the design and testing, and result in reporting of online-administered scales to assess the mental health effects of the COVID-19 pandemic.